IMMU-45. CUSTOMIZED LIPID NANOPARTICLES DELIVER NUCLEIC ACIDS TO IMMUNE CELLS IN BRAIN TUMORS. (9th November 2020) - Grippin, Adam; Wummer, Brandon; Mendez-Gomez, Hector; Wildes, Tyler; Dyson, Kyle; Dobson, Jon; Mitchell, Duane; Sayour, Elias
Abstract: BACKGROUND: Brain tumors are notoriously difficult to treat in part due to their isolation behind the blood brain barrier and their power to suppress antitumor immune responses. We have previously reported cationic liposome formulations capable of delivering immune modulatory nucleic acids to immune cells in various peripheral organs, but there is currently no reliable method to deliver nucleic acids into brain tumors without direct injection into the tumor site. OBJECTIVE: Here, we report the development of a customized lipid nanoparticle to deliver immune modulatory nucleic acids to immune cells in brain tumors. APPROACH: Cationic liposomes composed of varying lipid combinations were evaluated for their ability to deliver functional mRNA and siRNA to innate immune cells in vitro and in intracranial tumor models. Nucleic acids were labelled with Cy3 to monitor particle distribution in vivo . RESULTS: Lipids composed of DOTAP and cholesterol selectively delivered mRNA and siRNA to intracranial GL261 and KR158b tumors. Interestingly, these particles selectively delivered these nucleic acids to CD45+ white blood cells with minimal delivery to CD45- tumor cells or normal brain tissue. Encapsulation of siRNA blocking programmed death ligand 1 (PDL1) significantly reduced PDL1 expression on innate immune cells in brain tumors, with the greatest effects on tumor-associated macrophages. Co-administration of systemic checkpoint blockade with intravenous administration of these lipid nanoparticles bearing PDL1 siRNA enabled systemic and intratumoral checkpoint blockade, leading to 37% long term survivorship in an otherwise fatal intracranial tumor model. CONCLUSIONS: Our customized lipid nanoparticles enable potent intratumoral immune modulation via delivery of nucleic acids to immune cells in brain tumors.